PREDIKSI KINERJA JALAN TERKAIT ESTIMASI KERUGIAN PENGGUNA JALAN SELAMA MASA REKONSTRUKSI JALAN - Sudarsana, Dewa Ketut; Sulistio, Harnen; Wicaksono, Achmad; Djakfar, Ludfi (FSTPT Indonesia, 2015)
The low standard of National road is continuously reconstructed to establish Trans National connectivities. During the reconstruction period, the loss of road user costs and the negative impacts for surrounding environment were inccurred. Predicted losses of road users have not been conducted, so that it is important to be investigated. Initially, road performances were analyzed during road reconstruction. The road performances were analyzed using a descriptive method. Road performance variable includes running costs referred to the Bina Marga guidelines of Pd - T-15 -2005- B. National road reconstruction project in fiscal year 2013 is used as a case study. The results of the analysis are obtained as follows: 1) speed (Vm) can be predicted from the exponential relationship model in which degree of saturation in pre-reconstruction (DSp) is used as a generator variable. This generator variable is predicted declining at 6 km/h (DSp = 0.1); 2) The traffic flow (Qm) is predicted by multiplying the current pre-reconstruction flows with a factor of Fq. Traffic flows is predicted declining by 28% (Fq = 0.72); and 3) The degree of saturation (DSm) is predicted by a factor of Fds and estimated to increase by 30% (Fds = 1.3).